Evaluating the Efficacy of Nerve Blocks in Chronic Pain: A Comprehensive Systematic Review - Martin Gabe Tua Sihotang; Ida Bagus Krisna Jaya Sutawan (The International Journal of Medical Science and Health Research, 2025)
Introduction: Chronic pain, defined as persistent pain lasting beyond three months, represents a formidable global health challenge, contributing to profound disability, diminished quality of life, and immense socioeconomic burdens. Within the multidisciplinary management armamentarium, interventional pain management techniques, particularly nerve blocks, have emerged as critical therapeutic options for patients unresponsive to conservative measures. However, the literature on the efficacy of these procedures is characterized by significant heterogeneity, with variable reported success rates, durations of benefit, and levels of evidence across different anatomical targets and chronic pain conditions. This necessitates a comprehensive, systematic, and critical synthesis of the available evidence to guide clinical practice and future research directions (Manchikanti et al., 2024; Kaye et al., 2015; Boswell et al., 2015). Methods: This systematic review was conducted following a rigorous, multi-stage methodology. Across PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library. For the final report, the 40 sources with the highest screening scores were synthesized. Results: The synthesis of 40 high-quality sources reveals a nuanced landscape of efficacy. For spinal facet joint pain, therapeutic lumbar and cervical medial branch blocks, especially when preceded by positive diagnostic blocks, demonstrate Level II evidence for sustained, long-term improvement. RCTs report 82-90% of patients achieving ≥50% pain relief at 2-year follow-up, with each treatment providing a mean relief duration of 15-19 weeks, necessitating approximately 3-6 treatments over two years for sustained benefit (Manchikanti et al., 2007, 2008, 2010; Falco et al., 2012). Radiofrequency neurotomy for facet joint pain shows good to Level II evidence (Janapala et al., 2021). For chronic migraine, greater occipital nerve blocks (GONB) demonstrate significant efficacy, with meta-analyses showing a pooled reduction of 3.6 headache days per month and a 2.2-point reduction in pain severity (Shauly et al., 2019; Mustafa et al., 2024). In knee osteoarthritis, genicular nerve radiofrequency ablation (GnRFA) shows moderate-certainty evidence, with approximately 51% of patients achieving ≥50% pain reduction at 6 months; notably, large lesion techniques (55% success) significantly outperform small lesion techniques (34% success) at 12 months (Kanjanapanang et al., 2025; Zeitlinger et al., 2019). For vertebrogenic low back pain with Modic changes, basivertebral nerve ablation (BVNA) shows robust superiority over standard care (RR 4.16 for ≥50% pain reduction) but a much more modest advantage over sham procedures (RR 1.25), indicating a substantial placebo component (Khalil et al., 2019; Conger et al., 2021). Suprascapular nerve blocks are superior to both placebo (SMD=0.70) and physical therapy (SMD=0.75) for chronic shoulder pain at 12 weeks (Chang et al., 2016). Epidural steroid injections show variable evidence, with transforminal approaches having stronger long-term support for radicular pain than interlaminar approaches (Abdi et al., 2007). Specialized blocks for cancer pain (splanchnic neurolysis) and other conditions (cryoneurolysis, impar ganglion block) also show promising results. The safety profile across all modalities is favorable, with minimal serious adverse events reported. Discussion: The discussion reconciles the apparent heterogeneity in findings by analyzing key moderating variables. Efficacy is profoundly context-dependent, influenced by anatomical precision, technical parameters (e.g., lesion size in GnRFA, approach in epidurals), and rigorous patient selection via diagnostic blocks. A universal finding is the temporal decay of therapeutic effect, underscoring that nerve blocks often provide time-limited relief, logically leading to a paradigm of planned, repeat interventions for chronic conditions. A critical appraisal reveals the powerful influence of the placebo effect, particularly evident in BVNA trials, and highlights concerns regarding evidence quality, including potential bias from industry funding and a relative paucity of high-quality, independent, long-term, sham-controlled RCTs. The evidence hierarchy established allows for condition-specific, evidence-based recommendations. Conclusion: Nerve block interventions are effective and safe for a range of specific, well-defined chronic pain conditions, including facet joint-mediated spinal pain, chronic migraine, knee osteoarthritis (with optimized technique), and vertebrogenic back pain. However, their benefits are frequently not permanent, and optimal outcomes depend on accurate diagnosis, precise technique, and realistic expectation management involving potential repeat treatments. Future research must prioritize independent, sham-controlled RCTs with long-term follow-up, direct comparative effectiveness studies, and investigations into predictive biomarkers to personalize therapy.